Innovation methods, algorithms, and software for analysis of reinsurance contracts - Silvestrov, D.; Teugels, J.; Masol, V.; Malyarenko, A. (Інститут математики НАН України, 2006)
A Monte Carlo based approach to evaluate and/or compare the riskiness of reinsurance treaties for both the ceding and the reinsurance companies is introduced. An experimental program system Reinsurance Analyser based on the indicated approach is presented. The program allows analyzing
applications of a large set of reinsurance contracts under a variety of claim ﬂow models. The effect of applications is compared by risk measures, provided that the parameters of the contracts are balanced by an average reinsurer’s load quantity.